The Nexus of Remittances, Imports, and Private Investments with Nepal's Economic Expansion - Kadel, Dhaka Ram; Patodiya, Pawan Kumar (A Bi-annual South Asian Journal of Research & Innovation, 2023)
This study examines the nexus of remittances, imports, and private investments with Nepal’s economic expansion. The study uses annual data from mid-July 1976 to mid-July 2022. Gross domestic product (GDP) at a constant price is considered an indicator of economic expansion. The data is processed for the long-run connection adopting the bound testing technique of autoregressive distributed lag (ARDL), and the short-run trends are confirmed by deploying an error correction model (ECM) generated from the ARDL model. The Granger causality test determines the cause-and-effect connection. The evidence-based findings from ARDL establish that the link between Nepal's GDP and remittances is positive and insignificant in the short and long spans of time, while it is significant as well as positive with imports. It is, however, negative and insignificant with private investment. Similarly, unidirectional causation connecting GDP and remittances, imports and GDP, and remittances and private investments is demonstrated by the Granger causality evaluation.